Structure and Photoluminescence of Eu2+ Doped Sr2Al2SiO7 Cyan-Green Emitting Phosphors. (3rd December 2014) - Lu, Fa-Chun; Bai, Li-Jing; Dang, Wei; Yang, Zhi-Ping; Lin, Peng
Abstract : Eu 2+ doped Sr2 Al2 SiO7 cyan-green emitting phosphors have been synthesized with solid-state reaction method. With Rietveld refinement technique, Sr2 Al2 SiO7 equivalent sites and atomic positions were acquired. The Sr2 Al2 SiO7 :Eu 2+ photoluminescence at room and high temperature were investigated. This phosphor shows the Eu 2+ broad band excitation and emission spectra corresponding to Eu 2+ transitions between the 4 f  7 ground state and the lower 4 f  6 5 d 1 crystal splitting states. The luminescent properties as a function of Eu 2+ concentration were investigated. The mechanism of dipole-dipole interaction dominates the non-radiative energy transfer between the Eu 2+ luminescent centers and causes the concentration quenching of this phosphor. The radiation re-absorption is proposed to be the mechanism for the emission red shift. The emission band shows slight blue shift with increased temperature. Sr2 Al2 SiO7 :Eu 2+ is a kind of promising blue to cyan emitting phosphor.